'n Fasiliteringsvaardighedeprogram vir verpleegdosente - F. Cilliers (AOSIS, 1992)
The aim of this study is to discuss the role of the nursing teacher as facilitator of psychological growth m the student, with reference to personality characteristics and skills. A facilitation skills programme is applied to a group of nursing teachers and evaluated by means of a pre, post and post-post psychometric evaluation on an experimental and a control group. Significant positive behavioural change manifested inflexibility in the application of values, feeling sensitivity, internal locus of control arid the interpersonal skills of respect, empathy, realness and concreteness. It is recommended that the facilitating role be extended as communication dimension in practical nursing.